Recent developments and characterization techniques in 3D printing of corneal stroma tissue. (20th April 2021) - Ulag, Songul; Uysal, Ebru; Bedir, Tuba; Sengor, Mustafa; Ekren, Nazmi; Ustundag, Cem Bulent; Midha, Swati; Kalaskar, Deepak M.; Gunduz, Oguzhan
Abstract : Corneal stroma has a significant function in normal visual function. The corneal stroma is vulnerable because of being the thickest part of the cornea, as it can be affected easily by infections or injuries. Any problems on corneal stroma can result in blindness. Donor shortage for corneal transplantation is one of the main issues in corneal transplantation. To address this issue, the corneal tissue engineering focuses on replacing injured tissues and repairing normal functions. Currently, there are no available, engineered corneal tissues for widely accepted routine clinical treatment, but new emerging 3D printing applications are being recognized as a promising option. Recent in vitro researches revealed that the biocompatibility and regeneration possessions of 3D‐printed hydrogels outperformed conventional tissue engineering approaches. The goal of this review is to highlight the current developments in the characterization of 3D cell‐free and bioprinted hydrogels.